Urban and Rural Sustainability: Divergent Concepts and Their Consequences for Marketing - Zulauf, Katrin; Wagner, Ralf (Frontiers in Sustainability, 2021)
Sustainability is a topic of increasing social and scientific interest. Most sustainability innovations are adapted to the needs of urban areas. These innovations are either not offered at all in rural areas (e.g., car sharing) or require massive effort and restrictions to be usable or effective (e.g., ride sharing). Delving deeper than the description scholarly research needs to clarify consumers’ conceptualization of sustainability in urban and rural areas. Notably, the extent to which sustainable innovations are adopted and their associated adoption dynamics with the consequences for marketers, consumers and society differ between urban and rural. Two research questions are pressing: (i) How do conceptualizations of sustainability differ between rural and urban citizens? (ii) Which consequences for sustainable marketing management arise from differences and similarities of upstream innovations with downstream dynamics in urban and rural areas? Despite the wide range of previous research, the question of whether consumers living in urban and rural areas have a similar understanding of “sustainability” has not been comprehensively addressed. We address the literature on both the attitude-behavior gap in sustainability and Value-Belief-Norm Theory. This provides researchers with guidance to reveal divergences in values, motives and enablers for sustainability among people in urban and rural areas, which lead to different marketing approaches as a consequence. Studies that deepen the understanding of how innovative service and product offers need to be designed to the specificities of urban and rural environments, contribute to clarifying consumers’ attitude-behavior gap.